2020
DOI: 10.4236/ojmm.2020.102005
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of the Ethanolic Extract of <i>Crateva adansonii</i> DC. (Capparidaceae) Harvested in Dassa-Zoumè in Central Bénin

Abstract: Objective: The present was initiated to study the antibacterial properties of the Crateva adansonii DC extract on germs commonly identified in skin and digestive infections in Benin as well as the reversion of resistance to these aforementioned germs. Method: The bacteria's sensitivity test to extracts was carried out by the microdilution method in liquid medium as well as the MIC and the reversion of bacterial resistance. For the determination of the MBC, this technique is used coupled with spreading on agar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Characterisation of the antibacterial effect of Crateva adansonii (Capparidaceae) revealed that the aqueous mixture had a bactericidal effect on all the strains tested. This result differs from those obtained by [7] who, using the same plant, had indeterminate, bacteriostatic and bactericidal effects respectively on 50%, 25% and 25% of the germs tested.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Characterisation of the antibacterial effect of Crateva adansonii (Capparidaceae) revealed that the aqueous mixture had a bactericidal effect on all the strains tested. This result differs from those obtained by [7] who, using the same plant, had indeterminate, bacteriostatic and bactericidal effects respectively on 50%, 25% and 25% of the germs tested.…”
Section: Discussioncontrasting
confidence: 99%
“…It also contains secondary metabolites such as total tannins, total flavonoids and total phenolics in varying proportions, and has antioxidant properties that vary according to the concentration of the extract [4] [5]. Research by [5] [6] [7] has also shown that Crateva adansonii has antibacterial properties against germs commonly identified in skin and digestive disorders, such as Escherichia coli, Staphylococcus aureus, Proteus mirabilis and Pseudomonas aeruginosa. In Benin, Crateva adansonii is used to treat arterial hypertension [6], diarrhoeal diseases [8] and diabetes in pregnant women in Cotonou [9].…”
Section: Introductionmentioning
confidence: 99%